Nanofibrous morphology of electrospun chitosan nanocomposites reinforced with WS2 nanotubes: A design-of-experiments study. (July 2018) - Baklavaridis, Apostolos; Zuburtikudis, Ioannis; Panayiotou, Costas
Chitosan nanofibers reinforced with tungsten disulfide inorganic nanotubes (INT-WS2 ) were fabricated in this study. The aim was to investigate the effect of the material parameters and the electrospinning process parameters on the obtained nanofibrous morphology of the mats. The INT-WS2 content, the polymer solution concentration, the electric field strength, and the solution's flow rate were the investigated factors within the framework of response surface methodology. Scanning electron microscopic and image analysis were used for the dimensional characterization of the nanofibrous morphology and the estimation of three selected responses. Two responses were related to the quality of the nanofibrous morphology: the number surface density of the beads ( N bead ) and the average bead-to-fiber diameter ( D bead / D fiber ). The third response was indicative of the fiber thickness ( D fiber ). The developed models as well as the coupling and the individual effects of the four investigated factors are given. The results indicate that the electrospun nanofibrous morphology is mostly affected by the polymer solution concentration, the electric field strength and the INT-WS2 loading. Furthermore, the response-surface results reveal possible experimental pathways that may be followed in order to obtain specified nanofibrous chitosan/INT-WS2 morphologies.